THAILAND 4.0: A Macroeconomic Perspective in Modern Development - Luanglath, Inpong (Journal of Applied Economics and Management Strategy, 2018)
Thailand 4.0 is a development policy aiming to achieve economic prosperity, social well-being, human values and environmental protection. The goal of Thailand 4.0 is to transform Thailand into a First World Economy by 2032. This paper answers two research questions: (i) How far is Thailand from becoming a First World Economy? To answer this question, we use the 10-factor test of developed economy; and (ii) What does Thailand need to do in order to fulfill the requisite of economic sustainability? Secondary data used in this paper consists of annual reports of ADB, WEF and IMF. Kahnman-Tversky’s prospect theory was used to assess Thailand FEW characterization and economic sustainability. Ten common characteristics of the First World Economy were used to benchmark Thailand’s economy. Thailand scores 0.295 or achieved 29.5% probability of the expected value or succeeded 57.84% in achieving FWE status. According to the ADB’s partial indicators for sustainable economy, Thailand achieved 9 out of 20 indicators for sustainability. Thailand 4.0 is a road map for development, our findings provide the distance of reaching the country’s development target.